6
OK. If the x is a multiply symbol, -933
13+-12--5 = 6
Same as subtracting 6 from 7 = K
a= -0.8
6
It is: 3y-6
6
OK. If the x is a multiply symbol, -933
13+-12--5 = 6
Same as subtracting 6 from 7 = K
z + 8 - 2 is an expression, not an equation. An expression cannot be solved. At best, you can simplify it to z + 6.
a= -0.8
By multiplying out the brackets it then is -10+24t-48 = 24t-58 when simplified
Collect like terms: 9a -7a = 9 - 15, ie 2a = -6, so a = -3
-4
To simplify the expression 18 + 7x - 12 + 5x, you first combine like terms. Combine the constants (18 and -12) to get 6. Then, combine the x terms (7x and 5x) to get 12x. Therefore, the simplified expression is 6 + 12x.